Aktivitas antioksidan dan uji toksisitas ekstrak kulit batang kayu raru (Cotylelobium lanceolatum Craib) dengan menggunkan metode DPPH dan metode BSLT - Rossa, Aliffa; Daulay, Anny Sartika; Ridwanto, Ridwanto; Rahayu, Yayuk Putri (Journal of Pharmaceutical and Sciences, 2023)
Raru (Corylelobium lanceolatum Craib) is a group of endemic tropical forest plants from the Dipterocarpaceae family in Indonesia. Raru is a term for a group of types of bark added to palm sap, which aims to increase the taste and alcohol content of the drink. People in Sumatra believe that raru bark (Cotylelobium lanceolatum Craib) can be used as an antidiabetic drug. This study aims to determine the antioxidant activity of raru bark, the toxicity activity of raru bark extract, and the secondary metabolites in raru bark. This research was conducted in descriptive was born with a descriptive method. The sample used was raru bark. The research phase included sample preparation, plant identification, simplicial manufacture, antioxidant activity test, DPPH standard stock preparation, blank solution preparation, phytochemical screening, antioxidant activity test based on IC50, Toxicity test, and toxicity activity test based on LC50 value. The result obtained in testing the antioxidant activity of raru bark had an IC50 value of 94.25 µg/mL in the vary strong category. While the result of the probit analysis for the toxicity of raru bark extract using the BSLT method obtained an LC50 value of 350.9942 µg/mL. It is in the toxic category and has the potential to be an anticancer.